Forecasting Portfolio Risk Estimation by Using Garch and Var Methods - Noor Azlinna, Azizan; Lee, Chia Kuang; Zeenat, Ahmed (The International Institute for Science, Technology and Education, 2012)
Risk management or risk predicting are closely related with the market volatility which affect the return of portfolio estimation. Portfolio managers around the world concerned with risk estimation because portfolio risk management is part of their decision-making process. According to Hull (2006), VaR is widely used by fund managers “to provide a single number summarizing the total risk in a portfolio of financial assets.” Motivates from this, we conducted an analysis to compare the effectiveness of VaR analysis and GARCH method in forecasting risk estimation. Risk manager can used the best methods in reducing their customers risk volatility and rank the risk level.